0087 Evaluation of a change in bui penalties-lessons learned. (26th April 2015) - Peters, Marla
Abstract : Statement of purpose: Alcohol was a contributing factor in almost 30% of boating fatalities and 18% of injuries from 2005–2011 in Washington State. Washington's BUI law, unlike other states, did not require alcohol testing and did not punish refusals. In July, 2013, a revised BUI law went into effect. Washington state injury program and WA state Parks staff, along with staff from Seattle Children's received training in a APHA/Safe State Evaluation Institute in May, 2014. The team focused on Policy Evaluation of the new BUI law. Methods/Approach: The methods used were a mix of qualitative and quantitative: Pre/post data on number of citations and dispositions Key informant interviews with Marine Law Enforcement Officers Survey of County and City Prosecutors regarding use of the law Results: Results are in the process of being compiled and will be available by April 2015. Conclusions: We have learned the following about Policy Evaluation: Designate a person at the start of advocacy for Policy change to focus on evaluation, identify potential data sources and evaluation resources among partners in advocacy. Build a requirement for evaluation into any grant funding. Create an accurate Logic Model; it is central to Policy Evaluation. Incorporate differing perspectives of all partners into evaluation questions. Pose all questions, then sort through by availability of data and resources, by time frames, to narrow scope of evaluation. The final conclusions is that working as a team among all partners in the policy change is necessary to an effective evaluation. Significance and contribution to the field: This study provides a relevant framework for evaluating an innovative policy in real-time.